Application of Government Accounting Standards in Government Financial Reporting - Anggadini, S D; Agustin, N; Agustin, R S P; Zahrany, D N; Bramasto, A; Damayanti, S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine the influence of the application of government accounting standards and the role of internal audits on the quality of financial reports of municipal governments in Indonesia. The research approach used in this research is descriptive analysis with a verification approach. The sample selection is a saturated sample including 127 offices in Regional Apparatus Organizations in Indonesia. The data analysis technique used in this study is multiple linear analysis using SPSS 26.0 software. Based on the research, it can be seen that the application of government accounting standards affects the quality of local government financial reports. The role of Internal Audit influences the quality of local government financial reports in Indonesia. This research is expected to be used by intellectuals and interested parties, both the government and other parties who need information related to research. Therefore, an improved role of internal audit will lead to an increase in the quality of local government financial reports, where a strong internal audit role can have a positive impact on improving the quality of financial reports. It is recommended that stakeholders take a closer look at the reliability of the system and improvements in the management of internal audit to facilitate the process and implementation of internal audit.